Antiferromagnetic semimetal terahertz photodetectors enhanced through weak localization - Dong Wang; Liu Yang; Zhen Hu; Fang Wang; Yage Yang; Xiaokai Pan; Zhuo Dong; Shijian Tian; Libo Zhang; Li Han; Mengjie Jiang; Keqin Tang; et al. (Nature Communications)
Abstract Effective detection is critical for terahertz applications, yet it remains hindered by the unclear mechanisms that necessitate a deeper understanding of photosensitive materials with exotic physical phenomena. Here, we investigate the terahertz detection capabilities of the two-dimensional antiferromagnetic semimetal NbFeTe2. Our study reveals that the interaction between antiferromagnetic magnetic moments and electron spin induces disordered carriers to hop between localized states, resulting in a nonlinear increase in responsivity as temperature decreases. We integrate asymmetric electrodes to generate a sufficient Seebeck potential, enabling carriers to overcome the barrier of localized states and achieve reordering at room temperature. Additionally, the self-powered performance of the NbFeTe₂/graphene heterojunction is optimized by the built-in electric field, achieving peak responsivity of 220 V W-1 and noise equivalent power of <20 pW Hz-1/2. These results shed light on the potential of antiferromagnetic semimetals in large-area, high-speed imaging applications, marking a significant advancement in terahertz photonics.